Segmentation of Visitors Using Travel Motivation Approach at the Kuala Gandah National Elephant Conservation Center - Hassan, Suziana (2009)
Market segmentation has become an important tool in planning appropriate marketing strategies. It is a technique used to subdivide a heterogeneous market into homogeneous sub-groups based on the idea that a market is composed of sub-groups of people. While, nature-based product is widely adopted market using a travel motivation segmentation approach to differentiate the different criteria of visitors. The purpose of this study was to segment the nature-based tourists in KGNECC using their travel motivations which is able to recognize different types of nature-based tourist in relation to their travel attributes and characteristics. A survey was administered to a total of 401 samples of respondents using self-administered sampling design where they were asked to choose a statement related to their travel that correspond to nature-based tourist type namely as (1) ecotourist, (2) nature escapist, (3) comfortable naturalist, and (4) passive player. Multiple Discriminant Analysis (MDA) test was administered to segment and predict nature-based tourist types based on seven discriminator variables encompases of socio-demographic factor, trip characteristic factor, and travel motivation factor. Statitical analyses showed there are significantly relationship between the motivation factors and nature-based tourist groups (P<0.05).